Chemotherapy of carcinoma of the prostate and testis experimental study in vivo and in vitro - Okada, K (Hinyokika kiyo. Acta urologica Japonica, 1988)
Prostate cancer: Considering the stagnation in chemotherapy of prostate cancer in recent years, the following experiments were carried out to determine their clinical value. Surgical specimens from 6 patients, 2 permanent cell lines (EB 33 and PC 93) originated from human prostate cancer and a tumor line serially transplanted in nude mice (PC-NCC) were subjected to chemosensitivity tests such as human tumor cloning assay (HTCA) and/or in vivo tumor growth curve experiments using nude mice. The possible chemosensitive drugs screened by using surgical specimens and PC-NCC tumor were cisplatinum (CDDP), bleomycin (BLM), 5-FU, vincristine (VCR), adriamycin (ADM) and methotrexate (MTX). Most of these drugs were also judged as "effective" by HTCA using a permanent cell line. The minimal discrepancy among them may lead to the conclusion that an in vitro assay using a cell line can substitute for the assay using surgical specimens which can not be obtained frequently. Partly based on the data obtained a chemotherapy regimen, VPM-CisCF, consisting of VCR, peplomycin, MTX, CDDP, cytosine arabinoside (Ara-C) and 5-FU, was designed. The effectiveness of this regimen was demonstrated experimentally. Testis cancer: Two different lines of experiments were performed. A human testicular cancer serially transplanted in nude mice was repeatedly exposed to CDDP in vivo to obtain hyposensitivity to this drug. The synergistic effect of CDDP and VP-16 was demonstrated in the tumor thus obtained. One of its mechanisms has been suggested by partial accumulation of cancer cells in the G1-S and G2-M phase in which CDDP exerts its potential effect.(ABSTRACT TRUNCATED AT 250 WORDS)